Pengolahan Sampah Rumah Tangga Menjadi Kompos Pada Perumahan Lahan Sempit: Processing Household Waste Into Compost In Narrow Land Housing - Enni R. Sinaga; Siprianus Singga (Sanitation Departement of Health Polytechnic of Kupang, 2021)
The increase of household waste time to time leads to serious public health problem in daily life which is seriously not managed for instance the waste generated by household that would impact on pollutions and public health problems. The aim of this study is to measure the volume of generated waste and the waste volume which could be reducted by composting in household level. The mehthod of this study is an action research that conducted by measuring organic waste home composting, there are 25 houses are chosen as samples with some characteristics such as housewives as their work, collecting data is done by measuring household waste and waste management by tube system. The study results shows the volume waste generation of 25 houses resulted 366 litre per day. The waste volume can be reduced drastically to be compost to the level 52 litre per day. Therefore, if organic waste management is done by people in 264 units of simple houses /Rumah Sangat Sederhana (RSS) of Baumata Village , then organic waste could be reduced until 549 litre per day. The drastic waste reduction system is by planting the tube underground which the number of tubes per house is 10 pieces. The quantity of an organic waste which is generated by simple houses /Rumah Sangat Sederhana (RSS) of Baumata Village is 14.782 litre per day. Meanwhile household waste transportation is carried out once in every 3 days and the increase of waste volume until 10% then the 3 units of temporary waste disposal Centre (TPSS) needs with 3m3 the size of TPSS at the simple houses in Baumata Village. There was no TPSS found in the simple houses of Baumata Village and the community disposed of the waste both around their houses and outside the housing complex. This has an impact on disturbing esthetics and lead to breeding place for disease vectors and nuisance animals which lead to public health problems. The conclusion of this study is both organic Waste and inorganic waste volume generation from the household reached 366 liters per day and it can be reduced until 52 liters per day.